Análisis, diseño y construcción de un almacén de datos de colocaciones de crédito y captaciones de los bancos privados para aplicar algoritmos de minería de datos - Pezantes Angulo, Juan Carlos (2016)
This technical project aims to publicize data mining and applied to private entities for the purpose of discovering information that exists within the data useful, this information is handled through flat files that are publicly accessible, making with the results generated business opportunities in sites not yet overcrowded, increasing revenue and reducing expenditures for organizations. Data mining, you need to study and inquiry into their use and interpretation, also uses algorithmic tools for finding hidden information. This document consists of three chapters, where depth is detailed the relationship and utility proposed to grant proper use and handling of the data mining algorithms. Chapter one describes the tools and materials provided to begin the processing and analysis of information to further streamline the decision-making process. Chapter two describes the scientific and theoretical basis covered with artifacts and terminology used in project implementation. Chapter three describes the implementation of the data obtained and implemented in different data warehouses as well as the results of the study and application of data mining algorithms to predict future behavior in the business of each bank. Finally, they report for bank loans and deposits for them to be manipulated by people interested and are within the decision-making entities are generated.